Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae) - Ho, Hsuan-Ching; Last, Peter R. (Zootaxa, 2018)
A taxonomic review of species of the Indo–Pacific batfish genus Halicmetus occurring in the Australian Exclusive Economic Zone is provided. Treatments of six species in the region, including diagnoses of the widespread Halicmetus niger Ho, Endo & Sakamaki, 2008, H. reticulatus Smith & Radcliffe, 1912 and H. ruber Alcock 1891, a reclassification of the poorly known H. marmoratus Weber, 1913, and descriptions of two new species, H. westraliensis n. sp. (an Australian endemic) and H. drypus n. sp. (from the northern sector of the Australian Exclusive Economic Zone off Norfolk Island). The Australian species can be distinguished from each other and regional congeners by a combination of morphometrics, meristics and colouration. A key is provided for all known species of the genus.